1992
DOI: 10.2105/ajph.82.10.1365
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal tetanus in rural Bangladesh: risk factors and toxoid efficacy.

Abstract: OBJECTIVES. Tetanus continues to be a leading cause of neonatal death in Bangladesh as in other developing countries, yet little is known about risk factors or the efficacy of tetanus toxoid in this setting. METHODS. In May 1990, mothers of 6148 infants born alive between March 15, 1989, and March 14, 1990, in 30 rural unions of Rajshahi Division in Bangladesh were interviewed. Three surviving controls for each neonatal tetanus death were matched for sex, residence, and date of birth. RESULTS. Of 330 neonatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 7 publications
2
20
0
Order By: Relevance
“…18 Similar study performed in our country revealed untrained birth attendant and lack of hand washing as two of the most significant risk factors . 10 We observed that 60% of our neonates had at least one substance applied to the cord. In comparison to other Bangladeshi study 10 we found no neonate with cowdung application.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…18 Similar study performed in our country revealed untrained birth attendant and lack of hand washing as two of the most significant risk factors . 10 We observed that 60% of our neonates had at least one substance applied to the cord. In comparison to other Bangladeshi study 10 we found no neonate with cowdung application.…”
mentioning
confidence: 74%
“…Though we have good surveillance system for vaccine preventable diseases, still there are chances of underreporting. Though the condition described in previous study 10 done 22 years back has been improved a lot, still many neonates are taken to traditional healers for any convulsion or spasticity. Many neonates with illness may not reach the health care facilities.…”
Section: Discussionmentioning
confidence: 95%
“…Eight per cent of the NNT cases in the present study were babies delivered by the mothers who had received two doses of tetanus toxoid immunization during pregnancy. A case-control study conducted in rural Bangladesh found that the risk of NNT was not reduced by receiving two doses of tetanus toxoid (TT2) (Hlady et al,1992). They estimated the efficacy of TT2 at 45% and emphasized the need for improved quality of tetanus vaccine in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…92 Subsequent observational and case-control studies assessing the effect of tetanus toxoid on neonatal tetanus incidence or mortality have consistently noted vaccine effectiveness to be 80% or better, 74,115,131,153,154 except when subpotent tetanus toxoid vaccine was inadvertently used. 128 Although no studies designed to measure the effect of tetanus toxoid on maternal tetanus are available, a hospital-based study in Vietnam, where the vaccination of women has been vigorously promoted, showed a 90% reduction in tetanus in women aged 20-40 years. 39…”
Section: Distribution a N D Riskmentioning
confidence: 99%
“…Preference was given to articles published in the past 10 years. Animal dung used for fuel 126 †,129 Traditional substances used during labour, delivery, or abortion (ie, cow ghee* and other animal or vegetable oils,* juices or herbs) 121 Young maternal age or first pregnancy,* or bo t h 120 †, 12 3, 1 37 † Cultural constraints to women's movements and contacts 124,138 Other factors Death of a previous child in a family from neonatal tetanus (predictive of subsequent cases)* 122 †, 12 5 †, 126 †, 128 † Male sex (increased risk of neonatal tetanus) ‡ 2…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%